Why youths choose to become volunteers: from the perspective of belief - Arif Shah, Jasmin; Suandi, Turiman; Hamzah, Siti Raba'ah; Ismail, Ismi Arif (Social Sciences Division of the Athens Institute for Education and Research, 2015)
The purpose of the paper is to examine the engagement of youth in volunteerism and looks at the belief factor underlying youth participation in volunteering activities. Data were collected from the respondents using personally administered questionnaires. A survey was carried out from May to September 2013 involving 342 randomly selected respondents. The respondents ages between 15 – 40 years (M age = 24.8, SD = 4.7). The results indicated 69.9% (M=2.6930, SD=.47446) of the respondents attributed their participation in volunteerism to the belief factor. The level of belief in volunteering was high among youths. However, it should be noted that the factor may vary according to the needs of each individual. Only 0.6% of the youths had low belief in volunteering activities. The findings of the present study might be useful to volunteer organizations in helping them design interventions to boost volunteerism.